WAYS OF OPTIMIZING LAND RELATIONS OF AGRICULTURAL ENTERPRISES (INNOVATIVE ECONOMY, 2023)
Humeniuk М.M., Nemish D.V., Smushak M.V. WAYS OF OPTIMIZING LAND RELATIONS OF AGRICULTURAL ENTERPRISESPurpose. The purpose of the article is to highlight the ways of optimizing land relations of agricultural enterprises in view of the transformational processes taking place in the context of the formation of the land market.Methodology of research. Legislative and other normative legal acts, scientific works of domestic and foreign scientists on issues related to the problems of organization and optimization of land relations of agricultural enterprises became the theoretical and methodological basis of the research. The following general scientific and special methods were used to solve the tasks: abstract and logical - during the formation of theoretical generalizations, assumptions, and the formation of conclusions; analysis and synthesis - when evaluating the organization of land relations of agricultural enterprises, substantiating the conditions for the purchase of agricultural land by their participants; comparative analysis – when comparing the domestic and foreign experience of organizing land relations; analytical groupings - when justifying the differentiation of the concentration of land in the same hands depending on zonal features.Findings. The organization of land relations in economic entities with different forms of ownership and organizational and legal form of economic management is considered. The main problems of effective land use of agricultural enterprises have been identified. The expediency of mortgage lending and the functioning of the land bank are revealed. The expediency of differentiating the concentration of land in the same hands depending on the zonal features of one or another region is substantiated. On the basis of the identified features, the conditions for the purchase of agricultural land are characterized by the participants of the appointment of agricultural enterprises. The minimum and maximum threshold of lease terms is specified based on foreign experience and Ukrainian realities. It is proposed to differentiate the amount of rent depending on the size of the enterprise and the term of use of the land plot. The main aspects of state policy in the field of improving land relations are defined and outlined.Originality. A systematic approach was used to substantiate the improvement of land relations of agricultural enterprises in order to increase the efficiency of their management.Practical value. The obtained results of the research are the basis for solving practical problems regarding the determination of conditions for the purchase of agricultural land by agricultural enterprises, the establishment of rent and lease terms.Key words: land relations, land market, land lease, agricultural enterprise.
Keywords: land relations; land market; land lease; agricultural enterprise